Computer organization : principles, analysis, and design - Jin, Lan.; Hatfield, Bo (Singapore : Cengage Learning Asia Pte Ltd, 2014)
Written for an undergraduate course on computer organization for computer science and computer engineering majors, the depth and breadth of coverage of the book are suitable for both academic teaching in colleges and universities and reference by computer professionals and specialists. Computer Organization assumes that the reader has only a preliminary knowledge of a computer, but it thoroughly discusses the basic design principles and methodologies of the major functional units of a computer. The book features an analytical approach to all aspects of modern computer design the design of all major functional units of a computer is learned by way of the analysis of their characteristics. It presents the detailed design process of these functional units and especially their interconnection to construct the datapath and the control unit of a computer. The last chapter of the book discusses the design of the contemporary high-performance pipelined processor. The authors have chosen the material and its presentation carefully, hoping that they can fit the needs of readers with various areas of specialization and also the specific demands of various academic curricula.
1. Introduction -- 2. The Representation of information on a computer -- 3. Logic design of combinational circuits -- 4. Logic design of sequential circuits -- 5. The Arithmetic logic unit -- 6. Complex arithmetic operations -- 7. Instruction set architecture -- 8. The Central processing unit -- 9. The Control unit -- 10. Primary memory -- 11. Input/output (I/O) -- 12. Pipelining.
Includes bibliographical references and index.
Keywords: COMPUTER ORGANIZATION